Ocular Tuberculosis with Multiple Cerebral Abscesses. (26th March 2012) - Nor-Masniwati, Saidin; Zunaina, Embong; Azhany, Yaakub
Abstract : A 23-year-old Malay man presented with headache for one-month duration. It was associated with painless blurring of vision of the right eye. He had loss of appetite and reduced weight but no night sweats or hemoptysis. His visual acuity on the right eye was 6/45 and improved to 6/15 with pinhole. Right fundus examination revealed a choroidal tuberculoma located at one disc diameter away from optic disc superiorly with mild vitritis. Systemic examinations revealed no significant finding. Mantoux test reading was 22 mm with erythrocyte sedimentation rate that was 14 mm/h. Other blood investigations were negative with normal chest radiography. The computerized tomography scan of the brain revealed multiple cerebral abscesses. A clinical diagnosis of right ocular tuberculosis with multiple cerebral abscesses was made. He was treated with antituberculosis chemotherapy for one year which divided into intensive phase for three months and maintenance phase for nine months. Cerebral abscesses resolved after three months of antituberculosis drugs and at one-year follow-up, and the choroidal tuberculoma resolved completely with scar formation and significant macular striae.